2024
DOI: 10.1111/tpj.16614
|View full text |Cite
|
Sign up to set email alerts
|

‘Against all floods’: plant adaptation to flooding stress and combined abiotic stresses

Tilo Renziehausen,
Stephanie Frings,
Romy Schmidt‐Schippers

Abstract: SUMMARYCurrent climate change brings with it a higher frequency of environmental stresses, which occur in combination rather than individually leading to massive crop losses worldwide. In addition to, for example, drought stress (low water availability), also flooding (excessive water) can threaten the plant, causing, among others, an energy crisis due to hypoxia, which is responded to by extensive transcriptional, metabolic and growth‐related adaptations. While signalling during flooding is relatively well un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 232 publications
0
3
0
Order By: Relevance
“…1. Exploring plant perceptions and prioritization of responses to stress combinations: Studies have shown that one stressor will dominate under a stress combination, and plants will preferentially sense or respond to this primary stressor and react to it, involving complex signaling pathways [ 91 ]. The study of relevant pathways in plants will help us understand plant response mechanisms.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…1. Exploring plant perceptions and prioritization of responses to stress combinations: Studies have shown that one stressor will dominate under a stress combination, and plants will preferentially sense or respond to this primary stressor and react to it, involving complex signaling pathways [ 91 ]. The study of relevant pathways in plants will help us understand plant response mechanisms.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…While the molecular mechanisms of O 2 sensing in hypoxic conditions are well-described in Arabidopsis (e.g. reviewed in Le ón et al 2021;Loreti and Perata 2023;Renziehausen et al 2024), further research is needed on the specific signalling pathways and the molecular regulation of traits conferring hypoxia tolerance, as well as their functional characterisation and translation of such resources into flooding-sensitive crops. Excitingly, excellent examples of the use of molecular tools characterising genes responsive to hypoxia, tissue metabolic responses to hypoxia, tissue O 2 status, anatomical changes facilitating effective O 2 diffusion, and whole-plant responses to waterlogging, partial or complete submergence, or a combination of flooding with other stress conditions are well described in this Collection on 'Flooding stress and responses to hypoxia in plants'.…”
Section: Transdisciplinary Researchmentioning
confidence: 99%
“…Since flooding impairs oxygen diffusion, aerobic respiration for providing energy equivalents is hampered or even blocked. To adapt, plants will induce an acclimation response, including activation of anaerobic respiration, a process which is under strict transcriptional control (Bailey-Serres et al, 2012; Renziehausen et al, 2024).…”
Section: Introductionmentioning
confidence: 99%